Developing Interactive Augmented Reality Learning Media to Introduce Chemistry Laboratory Equipment in Senior High School - Ahmat Dani; Muhammad Zamhari (Journal of Educational Chemistry (JEC), 2025)
This research aimed to describe the validity or feasibility value of developing a game-based augmented reality learning application to introduce chemical laboratory equipment. The application developed was AR-LAB (Augmented Reality Laboratory), combining augmented reality technology with quizzes. This research employed development research using Richey and Klein's theory, which contains three steps: planning, production, and evaluation. The results show that the product's validity by material and media experts was 91.67% and 91.67%, respectively, in the very good category. The teacher assessment provided an average score of 112.4 from the ideal maximum score of 120, with an ideal level reaching 93.60% in the very good category. Meanwhile, testing by ten students obtained the maximum score in the very good category. The successfully developed media has the advantage of introducing laboratory equipment in three dimensions that are affordable and easy for students to learn about chemical laboratory equipment.